2013
DOI: 10.3102/0013189x12471426
|View full text |Cite
|
Sign up to set email alerts
|

Fully Accounting for English Learner Performance

Abstract: This article presents a set of recommendations that promote a more nuanced, meaningful accountability policy for English learners in the next authorization of the Elementary and Secondary Education Act. The authors argue that the ESEA reauthorization must strengthen the law's capacity-building purpose so that federal, state, and local leaders support continued attention, direction, and innovation in effectively educating ELs. The recommendations put forth in this article focus on monitoring both current and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 14 publications
1
55
0
Order By: Relevance
“…While our findings are limited to a sample of 20 districts, our findings indicate that few districts took advantage of this opportunity in 2014-15. This trend is particularly concerning when considering ELs whose achievement and progress is not adequately captured by standardized tests as a result of their emerging English language proficiency (Hopkins, Thompson, Linquanti, Hakuta, & August, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…While our findings are limited to a sample of 20 districts, our findings indicate that few districts took advantage of this opportunity in 2014-15. This trend is particularly concerning when considering ELs whose achievement and progress is not adequately captured by standardized tests as a result of their emerging English language proficiency (Hopkins, Thompson, Linquanti, Hakuta, & August, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, "ELL" is only one of many labels used for students in this population over the last 50 years. Initially referred to as "limited English speaking" children in the Bilingual Education Act of 1968, the list of terms for ELL students now includes "Total English Learners" which is a more comprehensive term that comprises both currently identified ELLs as well as former ELLs that have been reclassified as English-proficient (Hopkins, Thompson, Linquanti, Hakuta, & August, 2013;San Miguel, 2004). We use "ELL" in this analysis to refer to students who were identified as and participated in an English language program for various time frames.…”
Section: Purpose and Location Of The Studymentioning
confidence: 98%
“…States are required to annually administer an English Language proficiency assessment to ELs via local educational agencies in order to meet accountability requirements that are determined by the Elementary and Secondary Education Act (ESEA). These guidelines are directly correlated to No Child Left Behind Act (NCLB) policies according to Hopkins et al (2013), and continued in ESSA (Burnette, 2016).…”
Section: Elp Assessments and Academic Content Assessmentsmentioning
confidence: 99%
“…Hauck et al (2013) August et al (2015). As suggested by Hopkins et al (2013), the districts must determine whether their ESL program meets the needs of all ELs in order to reach a proficiency level of English on these assessments. Hakuta (2014) concluded that significant relationships have been established between English language proficiency assessment and content assessment, and in response to that conclusion, the data of this study provided further knowledge that may serve as an opportunity to better develop an effective assessment system by determining if differences exists between English Learner and non-English Learner student achievement.…”
Section: Elp Assessments and Academic Content Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation